(untitled) (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
The existence of a generator set is very important if there is a reduction in the main electricity supply from PLN which is conducting a blackout or under repair, then the generator set becomes an alternative power supply for electricity backup that ensures all service units at PIP Makassar are not hampered. So the role of generator facility maintenance in supplying electricity sources is very much needed to support performance, so efficiency is needed in the maintenance management process, especially on the CAT C.32 type generator set with a power capacity of 800 KVA which supports all activities in the simulator and other units. The purpose of this study is to analyze the burden of electricity supply needs on the service unit and to find out the right actions in maintaining the generator set engine components in the simulator so as not to hinder activities towards the learning process. However, other rooms do not have adequate generator supply or are not even available at all maximally based on the needs of the room/unit but are only concentrated on the simulator generator set supply unit. This results in an overload on the generator set which can cause serious damage to its internal component system, which makes the engine and alternator work harder, and are at risk of overheating, decreased efficiency, and even functional failure. That there has been a use of electric current of 401,370 watts or 1,825 amperes (50%), the simulator of 267,320 watts or 1,215 watts (33%), the Workshop of 114,088 or 519 amperes (14%) and the Mosque of 37,600 watts or 171 amperes (5%), so that the availability of generator power is 800 KW and has exceeded the use of 94 amperes or 102% with the category of Attention or overload.